EFEKTIVITAS PENGGUNAAN MODEL JIGSAW DALAM PEMBELAJARAN MENGIDENTIFIKASI UNSUR-UNSUR DAN MENGINTERPRETASI TEKS DRAMA PADA SISWA KELAS VIII SMP NEGERI 1 NANGGULAN - Sherli Sherli Rahmawati (LP3M Universitas Muhammadiyah Muara Bungo, 2019)
There are two objectives of this study descriptively, namely to describe the extent of the tendency of the ability to identify elements and interpret drama texts in class VIII Nanggulan 1 Junior High School whose learning uses jigsaw models and conventional discussion models. Comparatively to find out the significant differences between the use of jigsaw models and conventional discussion models on the ability to identify elements and interpret drama texts. The population of this study amounted to 192 students. The research sample is a simple random sampling technique. Instrument for research on validity and reliability. The prerequisite test results for the distribution of values ​​are normally distributed and homogeneous. The results of the study increased students' distributions descriptively in identifying the elements and interpreting drama texts with the jigsaw model with a mean of 29.41 categorized as very high and with conventional discussion models averaging 28.03 also very high category. Comparatively, tcount is 2.758 and t table 1.998 so Ha is accepted and H0 is rejected.